Islamic microfinance and Sustainable Development Goals (SDGs): evidence from Bangladesh, Malaysia and Turkey - Md Saad, Norma; Wudil, Adamu Ahmed; Uddin, Md Nazim; Ismail, Yusof (Research and Scientific Innovation Society, 2025)
This study examined the impact of Islamic microfinance though its Islamic, social, and ethical goals, adoption of profit and loss sharing (PLS) modes (Musharakah, Mudarabah), non-PLS modes (Murabahah, Ijarah) and charity-based financing modes (Zakat, Sadaqah, Qard al-Hasan) on Sustainable Development Goals (SDGs). In addition, it examined the impact on household income, enterprise development as well as program and practice. This study utilized a quantitative research design to evaluate the impact of Islamic microfinance on achieving SDGs in Bangladesh, Malaysia, and Turkey. Responses were obtained from 367 participants, comprising of beneficiaries of Islamic micro-finances in the three selected countries, using a structured questionnaire developed and administered through Google Forms. The findings reveal that profit-and-loss-sharing (PLS) mode of Islamic microfinancing promote SDGs while other modes such as non-PLS and charity-based financing show limited contributions due to operational inefficiencies and short-term focus. Household, enterprise development as well as program practice impacts highlight the need for scalable and systemic interventions, as their current implementations do not consistently translate into broader SDGs achievements. Based on the findings of the study, the study recommended that Policymakers should encourage the adoption of PLS contracts, supported by regulatory frameworks that mitigate moral hazard and adverse selection problems in Islamic microfinancing.